2015
DOI: 10.3233/wor-141855
|View full text |Cite
|
Sign up to set email alerts
|

Successful collaboration between occupational health service providers and client companies: Key factors

Abstract: Abstract. BACKGROUND: Occupational health services (OHS) are often described as an important resource to reduce work-related diseases and improve the workplace. OBJECTIVE: This paper identifies key factors for successful collaboration between Swedish OHS providers and their client companies. METHODS: Interviews were carried out with representatives of 15 companies and their OHS providers. The interviews were transcribed and their content analyzed. RESULTS:The results revealed that successful collaboration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
0
18
0
3
Order By: Relevance
“…OHS was an important consultant partner and supervisor for educating managers and co-workers in health and issues related to working conditions. Research shows that collaboration between OHS and SSEs depends on a continuous dialogue and the willingness of OHS to adjust services flexibly to meet specific needs of their customers [37]. The fact that this health-promoting project created increased collaboration between OHS and the participating SSEs is interesting because both Norwegian and Swedish studies have found that OHS are mainly used for individual health examinations and employee health care [14,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OHS was an important consultant partner and supervisor for educating managers and co-workers in health and issues related to working conditions. Research shows that collaboration between OHS and SSEs depends on a continuous dialogue and the willingness of OHS to adjust services flexibly to meet specific needs of their customers [37]. The fact that this health-promoting project created increased collaboration between OHS and the participating SSEs is interesting because both Norwegian and Swedish studies have found that OHS are mainly used for individual health examinations and employee health care [14,36].…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish study showed that OHS providers did not develop a close relationship with their SSE clients [37]. Other research shows that OHS have problems in reaching out to SSEs in Norway as well as in Sweden [14].…”
Section: Workplace Health Management In Small-scale Enterprisesmentioning
confidence: 99%
“…There is a considerable risk that such circumstances contribute to insecurity about their independence among employees with a subsequent loss of confidence in the OHS provider. From this, it follows that OHS providers, when their only point of contact is the HR Department, also have limited access to actual workplaces and to local knowledge, experiences, activities, and discussions on health and safety (Schmidt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation and execution are necessary and the fact that well-established practices and routines in OHSM can be advantageous to a successful collaboration with an OHS provider has been identified in a study of OHS providers in the private sector (Schmidt et al, 2015). Even if the employer is free to organize and delegate the organization's OHSM, legislation is clear; where necessary, there is an obligation to use an independent OHS provider or other external resource (Swedish Work Environment Authority, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation